Researching Behind the Badge: Challenges and Politics for Emerging Scholars in Police Studies - Akbar, Hafiz; Nugraha, Rifqy Pratama; Putra, Bagus Adithya Maha (Jurnal Ilmu Kepolisian, 2024)
This study aims to find that the organizational structure and culture of the police have a significant impact particularly in terms of facilitating access, ensuring research independence, and developing long-term relationships. Police research has enabled the integration of grounded theoretical findings with the practical application of police strategies. However, scholars in police studies, especially those new to research, often face intricate dynamics and limitations, particularly concerning police culture and organizational obstacles. This paper seeks to examine the challenges and political barriers that new researchers have when studying the police. Employing an empirical qualitative approach, this study combines semi-structured interviews with six researchers who have different levels of expertise in police research. Additionally, auto-ethnographic reflections offer a thorough understanding of the subject matter. The research findings suggest that the organizational structure and culture of the police have a significant impact on research, particularly in terms of facilitating access, ensuring research independence, and developing long-lasting connections. We conclude by proposing that establishing an effective research collaboration with the police necessitates finding a balance between the interests of academics and the police institution. To achieve this, we advocate implementing mentorship programs that pair experienced researchers with junior researchers and create collaborative infrastructure to help new scholars.